How do researchers perceive problems in research collaboration? Results from a large-scale study of German scientists - Weinmann, Carina; Hückstädt, Malte; Meißner, Florian; Vowe, Gerhard (Frontiers in Research Metrics and Analytics, 2023)
In recent years, collaboration has become the norm in scientific knowledge production. Like other forms of collaboration, research collaborations (RCs) face specific problems that can jeopardize success. Against this background, the present study sought to gain a deeper understanding of the relevance of different collaboration problems and the interconnections among these problems. Building on previous insights into the most current problems, we addressed four major issues: 1) researchers’ perceived relative relevance of collaboration problems in their projects (in terms of their occurrence), 2) differences in these perceptions based on the type of RC (e.g., number of subprojects and collaboration mode) and 3) on the characteristics of researchers, and 4) the co-occurrence of collaboration problems. Based on a representative survey of leading participants of RCs funded by the German Research Foundation (n = 5,326), we found that researchers experienced collaboration problems (e.g. fairness and communication problem) only to a small degree, and there were almost no differences regarding their perceived relevance. Furthermore, there were almost no significant differences concerning the perceived relevance of these problems depending on the type of RC or the individual researchers. However, the findings did reveal specific patterns of co-occurrence (e.g. relationship and difference problem). The results suggest that previous research may have overstated the relevance of collaboration problems in RCs. Instead, it seems that at least in Germany, collaborative research works better than one might assume.